2010
DOI: 10.1212/wnl.0b013e3181fef115
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration and swallowing in Parkinson disease and rehabilitation with EMST

Abstract: Objective: Dysphagia is the main cause of aspiration pneumonia and death in Parkinson disease (PD) with no established restorative behavioral treatment to date. Reduced swallow safety may be related to decreased elevation and excursion of the hyolaryngeal complex. Increased submental muscle force generation has been associated with expiratory muscle strength training (EMST) and subsequent increases in hyolaryngeal complex movement provide a strong rationale for its use as a dysphagia treatment. The current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
327
0
27

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(361 citation statements)
references
References 37 publications
7
327
0
27
Order By: Relevance
“…Specific motor exercises that include the swallow and have been shown clinically to improve behavioral aspects of the swallow are the Mendelsohn Maneuver, the effortful swallow, and the Masako Maneuver (5,8,62). However, motor exercises that do not include a swallow such as progressive resistance tongue exercise with the Iowa Oral Pressure Instrument, expiratory muscle strength training, and the Shaker Head Lift have also led to improvements in strength and swallowing function (5,8,53,62,65,79). Therefore, we included aspects of learning and specificity in our study to further investigate their effects on the tongue musculature.…”
Section: Discussionmentioning
confidence: 99%
“…Specific motor exercises that include the swallow and have been shown clinically to improve behavioral aspects of the swallow are the Mendelsohn Maneuver, the effortful swallow, and the Masako Maneuver (5,8,62). However, motor exercises that do not include a swallow such as progressive resistance tongue exercise with the Iowa Oral Pressure Instrument, expiratory muscle strength training, and the Shaker Head Lift have also led to improvements in strength and swallowing function (5,8,53,62,65,79). Therefore, we included aspects of learning and specificity in our study to further investigate their effects on the tongue musculature.…”
Section: Discussionmentioning
confidence: 99%
“…Troche et al 5 reported that the airway protection was improved and the risk of penetration/aspiration were not found in the literature, which limited the theoretical study and discussion of this study. Thus, we suggest further studies addressing the use of IS related to the biomechanics of swallowing.…”
Section: Discussionmentioning
confidence: 78%
“…Steele et al 4 presented correlations between vertical and horizontal movement of this complex during swallowing and the predictive value for biomechanical of swallowing disorders. In this context, Troche et al 5 carried out a study in which they demonstrated the importance of respiratory muscle training, through the use of expiratory spirometry for the dysphagia rehabilitation in Parkinson patients. They verified that there was an improvement in the function of swallowing, being it attributed to the improvement of the hyolaryngeal complex function, resulting in an increased airway protection during swallowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This training protocol is based on a previous trial in individuals with Parkinson's disease with an extended training length 12. Training occurred in the patient's home, with nose clips in place to avoid nasal air emissions.…”
Section: Participant and Methodsmentioning
confidence: 99%